Antioxidant nutraceuticals : preventive and healthcare applications - Cao, Chuanhai; Pathak, Sarvadaman; Patil, Kiran (Boca Raton, FL : CRC Press, Taylor & Francis Group, 2018)
"This book addresses various clinical and sub clinical applications of antioxidant nutraceuticals, with a primary focus on preventive use for general wellness, common ailments, and such chronic illnesses as cancer and neurological applications. This unique book captures the applications of natural antioxidants, which have been used for thousands of years in Traditional Chinese Medicine and Ayurvedic Medicine as well as modern nutraceuticals formulations. It covers antioxidant applications in clinical scenarios including the historical perspective, basic antioxidant properties and applications, anti-inflammatory properties, and antioxidant applications in a variety of clinical conditions."--Provided by publisher
Foreword -- Series Preface -- Preface -- Antioxidant Nutraceuticals : Historical Perspective and Applications in Various Traditional Systems Worldwide / Chuanhai Cao and Kyle Sutherland -- Antioxidant Nutraceuticals : Present Market and Future Trends / Adryan Perez, Richard Nguyen, Ailyn Valladares, and Sarvadaman Pathak -- Antioxidant Nutraceuticals and Prostate Cancer / Zhijun Wang, Patrick Chan, Chen Xie, Ying Huang, and Jeffrey Want -- Natural Antioxidants in General Cancer Prevention / Avipsha Sarkar and Shampa Sen -- Antioxidant Nutraceuticals, Alzheimer's Disease, and Dementia / Nandini Doshi, Sarvadaman Pathak, and Kiran Patil -- Antioxidant Nutraceuticals and Parkinson's Disease / Adryan Perez, Andrew Tran, and Chuanhai Cao -- Nutraceutical or Food-Based Antioxidants for Depression / Oyinlola Adeyanju, Thomas Towers, and Thea Moore -- Antioxidant Nutraceuticals and Preeclampsia / Monika M. Wahi -- Antioxiidant Nutraceuticals with Probiotic Applications / Arpita Das and Runu Chakraborty -- Antioxidant Nutraceuticals as Health Drinks for Prevention of Diseases / Kumar Rajendran, P. Latha, and Shampa Sen -- The Prevention and Treatment of Coronary Heart Disease and Congestive Heart Failure with Antioxidants and Nutritional Supplements / Mark C. Houston -- Nutraceuticals : A Preventative Measure against the Adverse Impact among Diabetic Patients / Suyansh Sharma and Sarvadaman Pathak -- Antioxidant Nutraceuticals : Novel Strategies for Combating Chronic Inflammatory Diseases / Adeleke Badejo and Ashim Malhotra -- Immunomodulation and Antioxidant Nutraceuticals / Gregory L. Smith -- Free Radicals and Antioxidants in Better Healthcare / Shannon Kelly and Rohini Nimbalkar -- Pharmacology and Pharmacokinetics of Natural Antioxidants in the Human Body / Aishwarya Potdar, Danielle Dantuma, Charles Preuss, and Yashwant Pathak -- Antioxidant Nutraceuticals and Skincare / Bell Loo, Hiep Nguyen, and Uyen Le -- Catechins as Potential Therapeutic Agents for Ocular Diseases / Radouil Tzekov, Shannon Kelly, and Anjali Hirani -- Antioxidant Nutraceuticals for the Prevention and Treatment of Acute and Chronic Lung Diseases : Current Trends and Future Prospects / Manish Bodas, Garrett Pehote, and Neeraj Vij
Includes bibliographical references and index
Keywords: Functional foods; Antioxidants; Alternative medicine